BACTERIOLOGICAL STUDY OF THE MARINE WATER IN THE COASTAL OF THE NORTH SULAWESI PROVINCE, INDONESIA - Sutiknowati, Lies Lies (Makara Journal of Science, 2006)
The main objective of this research was to study the marine bacteriology of the coast of North Sulawesi. The study was accomplished by calculating the abundance of coliform, heterotrophic, and pathogenic bacteria, and analyzing the coexistence relationship between bacteria and phytoplanktons. This research, which included the sampling and laboratory works, has been carried out on 25 – 28 October, 2000. The results suggested that the abundance of each bacteria was as follows: coliform bacteria range between 227-5940 cfu/100 ml with averages 1814.1 cfu/100 ml, found in all stations; heterotrophic bacteria range between (1-82) x 103 cfu/ml with averages 12.1 x 103 cfu/ml, it was high density and has association with phytoplankton Trichodesmium thieubautii. It was also found 6 species of pathogen bacteria e.g. Aeromonas, Citrobacter, Proteus, Pseudomonas, Yersinia and Shigella. The presence of coliform and pathogen bacteria was indicator of low quality of the seawater in the sampling area. Based on bacteriological study, the North Sulawesi Coastal is not suitable for aquaculture and need treatment and controlled for further coastal exploitation.